IMPLEMENTASI GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DI SMP NEGERI 1 WAMENA KABUPATEN JAYAWIJAYA - Sitti Aisyah; Soltan Takdir (STKIP Pesisir Selatan, 2017)
This study examines the implementation of situational leadership style of Principal in Junior High School 1 Wamena Jayawijaya Regency. This type of research uses a descriptive qualitative paradigm approach. Research subjects will be determined based on purposive sampling, informants in this study as many as 7 (seven) people. Data collection is done by observation, documentation, indepth interview, data analysis is done by: data reduction; exposure to data (data display); and conclusion drawing / verifying. The results of the study show: 1) The principal has implemented situational leadership style, from the indicator of the principal acting as telling / executing, selling / peddling, participating / delegating / delegating, 2) the support factor of situational leadership style implementation is the principal always try to embrace all parties in carrying out their duties, be fair, provide motivation, the existence of human resources in accordance with the standards of competence, tersesdianya facilities and adequate school infrastructure. While the inhibiting factors among them are some difficult teachers in communicating with leaders, 3) Impact of implementation of situational leadership style of the principal in improving the quality of SMP Negeri 1 Wamena Jayawijaya Regency, which during this school gets the value of accreditation